PENGEMBANGAN MAJALAH ELEKTRONIK BIOLOGI BERBASIS MULTIMEDIA PADA MATERI PLANTAE KELAS X SMA/MA - Rendi Handika; Wan Syafii; Imam Mahadi (Universitas Lancang Kuning, 2022)
This study aims to produce a quality electronic biology magazine based on the assessment of a team of experts (media experts & material experts), educational practitioners, and student responses. The type of research used is research and development (R & D) using the ADDIE development model. Data collection techniques were obtained from media expert validation questionnaires, material expert validation questionnaires, practicality questionnaires and student response questionnaires. The instruments used are validation sheets, practical sheets, and student response test sheets. The data analysis technique used is the validity of electronic magazines, practicality of electronic magazines, and student responses to the results of developing electronic magazines. The results of the validation test by the validator resulted in an average score of 4.38 which was included in the very valid category. The average score of the teacher's practicality test questionnaire, which is 4.59, is included in the very practical category. The average score of student responses is 4.53 with a very good category. These results indicate that the developed biology electronic magazine is a quality product. Keywords: Electronic Biology Magazine, Multimedia, & Plantae